Wymiana gruntów rolniczych spółdzielni produkcyjnych: [Exchange of land owned by agricultural production cooperatives] (Studia Prawnicze / The Legal Studies, 1963)
The term “consolidation” indicates the purpose of this institution.This goal is achieved through large-scale exchange. The term “exchange of land” refers to the means of achieving the goal only and not to the goal as such.According to the decree of 16 August 1949, on the exchange of land, this exchange serves, above all, for the consolidation of land owned by the agricultural production cooperatives.With regard to the exchange of land owned by agricultural production cooperatives, the decree of 16 August 1949, setting the standards in this area, abolished the law of 31 July 1923 on consolidation of land. In case of lack of standards in the decree of 16 August 1949, the solutions are to be sought in the general legislation, and only in case of gaps in this legislation, the provisions of the law of 31 July 1923 enter into practice, by analogy. The regulations issued in connection with the decree of 16 August 1949 are invalid in the matters standardised by the sources of the law, and invalid in the area, in which the regulations address these issues differently.According to the provisions of the law of 17 February 1961 on cooperatives and their associations, land belonging to members, brought as deposits to agricultural production cooperatives, is linked only by economic relations and often still in an uncomplicated relationship. This state of affairs can only be changed by carrying out an exchange procedure. This procedure leads to the collection of land belonging to the members from an economic or legal point of view. In the second case, provided for in Art. 4 of the decree, a co-ownership appears, which has, in part, the features of a common co-ownership.This exchange may be undertaken on the motion of at least half of the owners of the land comprising the area to be exchanged. The exchange can also be carried out automatically.This does not, however, apply to the exchange based on Art. 4, para. 1 of the decree. The decisive resolution on exchange of land has a double effect: constitutional and declarative. The first, i.e. as to the matter possessed, is not subject to legal control; the second, i.e. as to the subject of the possession, the courts are not involved.According to the provisions of the law of 17 February 1961 on cooperatives and their associations, an individual who wants to claim the land receives the same land that was contributed to the cooperative. This individual may receive another plot of land only in the case, where the needs of the exploitation system of the complex oppose its restitution.